The Messiah before Jesus : the suffering servant of the Dead Sea Scrolls - Knohl, Israel (S. Mark Taper Foundation imprint in Jewish studies., 2000)
In a work that challenges notions that have dominated New Testament scholarship for more than a hundred years, Israel Knohl gives startling evidence for a messianic precursor to Jesus who is described as the 'Suffering Servant' in recently published fragments of the 'Dead Sea Scrolls'.